ANALISIS EDUKATIF CERPEN MISI MENYELAMATKAN JANTUNG AYAH KARYA WIDYA AZHARI - Kusuma Yuda, Ramadhan; Fitriani; Salsabila, Aurel Aulia (Universitas Hamzanwadi, 2026)
This study aims to analyze the educational value of the short story